Major Pests of Soybean Leaf - Yuldasheva Shokhista Kobiljonovna; Khamidov Abubakir Kodirjon oʻgʻli (Genius Publishing Group, 2023)
The article focuses mainly on information about the pests that damage soybean leaves. Information about some of them is also given.
Keywords: Soybean leaf; insects; eggs; White fly